If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 150p + -105 + 13p = 58 Reorder the terms: -105 + 150p + 13p = 58 Combine like terms: 150p + 13p = 163p -105 + 163p = 58 Solving -105 + 163p = 58 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '105' to each side of the equation. -105 + 105 + 163p = 58 + 105 Combine like terms: -105 + 105 = 0 0 + 163p = 58 + 105 163p = 58 + 105 Combine like terms: 58 + 105 = 163 163p = 163 Divide each side by '163'. p = 1 Simplifying p = 1
| l+4=16 | | -30=-3+1y | | 13x+72=-23x | | (4ab)(4ab)(4ab)= | | 4x^2+6x+2=90000 | | 3c+5+c=-6+4c+8 | | 16=7+n | | 17+-9y=-3+7y | | 6n=243 | | 8cos^2(x)-2=0 | | 15/-2h=15/12 | | 14+x=6 | | 4b^2-28b-120=0 | | 5c^2=35c | | x=4-5(6) | | x^3=93 | | 6-3v=3v-18 | | 4g+20=6t-13 | | 15x+6=75 | | 8-(-25+4)= | | 10x+19=3x+201 | | -2/7*x+6+1/7*x=18 | | 3/x+3=5/2x+6+2/x-2 | | 3x-3-4=x | | 2j+4=10j | | 3x-3-2=x | | -3(6b)+5b+8= | | 7x+2=6x-7 | | 3x-3-1.75=x | | 2x/3-6=5x | | -25*2= | | y=-1/3x+4 |